Analisis Kesalahan Siswa Kelas VII dalam Memecahkan Soal Matematika Model PISA Konten Uncertainty and Data - Husna, Ismil, Sri Rejeki, M.Pd.,M.Sc (2017)
This study is purposed to identify the error of students and factors cause in the solve the problem of mathematics model of PISA content uncertainty and data. The method of this study is qualitative descriptive. The subject of this study is students grade VII-H SMP Negeri 1 of Kartasura. Data collection technique using observation, test, and interview. Data analysis technique in this study is done for in the field using model Miles-Huberman, beginning with data reduction, presentation of the data, and ends with a withdrawal conclusion. Research instrument using the test consisting of 6 problems with the completion of using the problem solving strategies Polya. Students error analysis refers to Newman Error Analysis consisting of 4 categories are comprehension, transformation, process skill, and encoding. The results obtained the amount of the percentage of each type of errors, that error understand the problem 30%, error plan 18%, error enforce plan 53%, and error reexamine 74%. In general the error of factor is low student's ability to change a problem in the context of a real and skills in doing mathematical calculations. Major factor in the error is students not used to work on a matter of mathematics using step Polya in coherently.